Harmony in Halal: Understanding Stakeholder Views Analyzing Products and Evaluating Policies in Malaysia - Ahmad, Zaki; Mafaz, Mohamed Normen Ahamed; Rahman, Dr Md Mahfujur (West Science Business and Management, 2023)
This study examines Malaysia's crucial role in the global Halal market, focusing on stakeholder perspectives, product analyses, and policy evaluations. Interviews with key industry players and coupled with a phone interview reveal diverse insights. Stakeholders emphasize the industry's commitment to producing lawful consumer goods and highlight challenges in community understanding. The analysis of products sold in the Muslim market, excluding meat, unveils common non-Halal elements, underscoring the intricate balance required for Shariah law compliance. A detailed examination of Malaysia's Halal industry policies, covering certification procedures, auditing, and monitoring, highlights the nation's proactive approach. The study concludes that Malaysia's commitment, invigorated by the Halal Industry Development Corporation, significantly contributes to setting high global standards. By harmonizing stakeholder views, dissecting product realities, and evaluating policy effectiveness, this research provides a comprehensive understanding of Malaysia's Halal industry dynamics. The insights gleaned are valuable for academics, industry practitioners, policymakers, and consumers navigating the dynamic landscape of the Halal market.